IDENTIFIKASI CEMARAN BAKTERI SALMONELLA PADA GULA CAIR MENGGUNAKAN REAL TIME-POLYMERASE CHAIN REACTION DAN MEDIUM SPESIFIK - Putri, Melysa; Subriadi, Fejri; Syafrinal, Syafrinal; Hafnimardiyanti, Hafnimardiyanti; Armin, M. Ikhlas; Putri, Annisa (Politeknik ATI Padang, 2024)
The development of the food and beverage industry has led to an increasing demand for the availability of liquid sugar. To ensure the hygiene of liquid sugar products, quality control is necessary, one of which is through microbiological analysis. This study aims to identify the presence of Salmonella sp. in liquid sugar produced by PT XYZ using microbiological and genetic analysis methods. The methods applied include bacterial inoculation on Xylose Lysine Deoxycholate (XLD) agar as a specific medium and Real-Time Polymerase Chain Reaction (RT-PCR) to detect bacterial DNA. The results showed no color changes in the XLD medium that would indicate the presence of Salmonella sp. Additionally, the RT-PCR results did not show amplification in the samples, except for the positive control. This indicates that the tested liquid sugar products are free from Salmonella sp. contamination, demonstrating the effectiveness of good sanitation and storage practices during production.